Real option in action: An example of flexible decision making at a mine operational level - Ajak, A.; Topal, Erkan (Elsevier Ltd, 2015)
Flexibility and operational adaptability are essential for long term corporate success and real option (RO) appears suitable for analysing risky projects. Nevertheless, its application in engineering design has been slow-moving compared to financial uses. Therefore, there is a compelling argument for using visual, intuitive and transparent models, such as the binomial decision tree, which has the potential to eliminate decision maker apprehension and improve RO use in engineering design and decision making. This paper reviews RO applications in mining projects and proposes a new methodology to explore technical applications of RO in mine design and decision making at the mine operational level. The research will investigate the suitability of using the RO method at the mine operational level where production decisions are made frequently, rather than organisational strategies that are reviewed after several years. The proposed approach is applied to a case study. This will demonstrate how RO can be used in designing multiple pits in multi-zone ore deposits to create a switching option between pits regarding changing ore grades and fluctuating commodity prices. The main rationale of this option involves deferring waste materials by switching mining activities from a high to low strip ratio pit. This creates a choice between using new RO thinking and the traditional methodology. The option is analysed using the binomial decision tree. The results summarised in this paper's conclusion reveal that the project's value increased considerably when flexibility was included in the mine design. These increases in project value were between eight to 15 per cent, depending on the number of flexible options incorporated into the design.